Cartwheels by Natalie Schriefer - Schriefer, Natalie (Flash Frog, 2025)
Nick’s millionth cartwheel looks like his first: He plants one hand on the grass and then, before I can catch his legs and help, he tumbles into a round-off. For a moment I’m taller than him, and I…
Keywords: dept.hhs

Gay Romance ‘Heated Rivalry’ Is Reigniting a Troubling Debate - Schriefer, Natalie (Bloomberg.com, 2025)
Heated Rivalry, based on the second book in Rachel Reid’s “Game Changers” series, has been a hit for HBO Max. Critics have called the gay romance about hockey players one of the best queer TV shows, praising it as “sexy” and “significant.” Beyond these glowing reviews, though, there is another discourse. Heated Rivalry’s success has reignited an unhealthy debate over who gets to tell the stories of marginalized communities — a debate that has proven harmful to closeted creatives in the past and
Keywords: Art; Career; Environment; Equality; Jordan; NETFLIX INC; NEW YORK TIMES CO-A; Rachel Reid; TWITTER INC; Youtube; dept.hhs; view

What I Learned When I Refused to Give Up on My Most Challenging Yoga Pose - Schriefer, Natalie (Yoga Journal, 2025)
A lesson on leaning into discomfort.
Keywords: dept.hhs

Why a Home Yoga Practice Is Just as Legit as Studio Practice - Schriefer, Natalie (Yoga Journal, 2025)
At-home yoga taught me about flexibility—and perfectionism, too.
Keywords: dept.hhs

Why This Round of Tariffs Feels So Personal - Schriefer, Natalie (Bloomberg.com, 2025)
The dreaded “T” word seems to be on everyone’s mind because consumers know it could mean paying more for what they love.
Keywords: China; Donald John Trump; Lifestyle; Policy; Politics; Raw Materials; Small Business; Trade War; Video Games; White House; dept.hhs; view

Utilizing the program impact pathways framework for improving COVID-19 vaccine confidence and uptake: demonstrations of multi-sector collaboration from two geographies in Connecticut - Beaulieu, A.; LaMonaca, Katherine; Higginbottom, Jackson; Foster, Jaime; Macklin, Bernard; Muhammad, Tila; Schwartz, Elizabeth; Comerford, Beth; Santilli, Alycia; Duffany, Kathleen; Pérez‐Escamilla, Rafael (Vaccine, 2025)
Keywords: 2019-20 coronavirus outbreak; Biology; Coronavirus disease 2019 (COVID-19); Infectious disease (medical specialty); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); Virology; dept.hhs

Listening to Community to Improve Breastfeeding Friendliness: Findings From a Community Readiness Assessment on Breastfeeding - Frieson, Tomeka; Masterson, Amelia; Tran, Victoria; Douglass, Frankie; Duffany, Kathleen (Health Promotion Practice, 2025)
Breastfeeding is a key nutritional behavior for infants during their first years of life. While prenatal breastfeeding intentions do not differ significantly between non-Hispanic Black and White mothers, the ability to meet those intentions decreases over time, and to a greater extent among Black mothers. This is partially due to environments inadequately supportive of individuals' breastfeeding needs (i.e., not breastfeeding-friendly). The Community Readiness Assessment is a powerful tool to assess a community's readiness to take action on pressing health issues. While it is frequently used to understand readiness to prevent negative health outcomes, this study explores how it can be used to understand readiness to promote breastfeeding friendliness and subsequently identify appropriate intervention strategies. Between November 2020 and June 2021, we conducted interviews with 23 key respondents in New Haven, Connecticut, representing five community sectors. Respondents scored five dimensions of readiness on a 9-point scale (1 = no awareness, 9 = community ownership). The overall community readiness score was 4.2, denoting the "preplanning" stage of readiness. The highest-scoring readiness dimension was "community knowledge about the issue" (mean score: 4.5), and the lowest-scoring dimension was "resources related to the issue" (mean score: 3.3). Small business owners reported the highest readiness score by sector (mean score: 5.0), while large employers reported the lowest (mean score: 3.1). Scores stratified by both sector and dimension revealed specific areas within the community where readiness-level-appropriate interventions could be implemented. This study highlights the benefit of assessing community readiness prior to intervention to identify tailored, equitable, and effective intervention strategies.
Keywords: Active listening; Breast feeding; Breastfeeding; Breastfeeding promotion; Community Readiness Assessment; Community health; Intervention (counseling); Psychological intervention; Scale (ratio); breastfeeding; breastfeeding-friendly; community; community assessment; community readiness; dept.hhs; public health practice